To feel good you have to look good : representing women's experiences of cosmetic surgery and dermatology in Irish print and television media - O Malley, Mary-Pat (Trinity College (Dublin, Ireland). Department of Clinical Speech & Language Studies, 2012)
This thesis addresses research questions concerning representations in language of cosmetic surgery and dermatology in print and television media, including linguistic evidence of editorial influences in media texts. In addition to answering theses questions, it aims to ascertain if discourse analysis may inform body studies' theoretical approach to the topic of CSD by attending to specific linguistic aspects of mediated CSD discourses.
Keywords: Clinical Speech and Language Studies, Ph.D.; Ph.D. Trinity College Dublin.